The interaction of the active compounds of Labisia pumila on RANK–RANKL–OPG system. (February 2018) - Noor, Zairin; Kania, Nia; Azharuddin, Azharuddin; Budhiparama, Nicolaas; Nurdiana, Nurdiana; Hidajat, Nucky Nursjamsi; Fatmawati, Fatmawati; Setiawan, Bambang
Summary: The objective of this research was to analyze the interaction of the active ingredients in Labisia pumila (kaempferol, rutin, apigenin, caffeic acid, pyrogallol and gallic acid) against RANK–RANKL–OPG system in context of osteoporosis. This is an in silico research. The three-dimensional structure in .sdf file is converted to PDB format using the Open Babel 2.3.1 software. The three-dimensional structure model of RCSB RANK–RANKL and RANKL–OPG was obtained fromhttp://www.rcsb.org/pdb . The ligand–protein docking and visualization analysis was carried out with Hex8.0 and Discovery Studio Client 3.5 software. RANK–RANKL or RANKL–OPG complex has the easiest interaction with rutin. In conclusion, flavonoid compounds (rutin, apigenin, kaempferol) more easily interact with RANK–RANKL and RANKL–OPG systems than isofavonoid groups (caffeic acid, pyrogallol, gallic acid). This opens the opportunity for the utilization of flavonoid from L. pumila as antiosteoporosis. Highlights: In silico study of Labisia pumila . RANK–RANKL complex has the easiest interaction with rutin. RANKL–OPG complex has the easiest interaction with rutin.